Implementation of community-based tourism (CBT) in Coban Parang Tejo Malang - Siti Asiyah; Kartika Rose Rachmadi (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2020)
This study uses a qualitative descriptive approach with a SWOT analysis tool; namely Internal-external situation analysis which aims to determine the strengths and weaknesses as well as the factors that become opportunities and threats for the development of the Coban Parang Tejo tourism area in Malang, and the application and implementation of Community Based Tourism principles for the development of the Coban Parang Tejo tourism area. The results of the study concluded that the concept of CBT has been applied in tourism management in Coban Parang Tejo (CPT) which was applied in the form of local community participation, the formation of a tourism village institution, environmentally friendly tourism management, the role of government, cooperation with investors and the creation of community business activities. From the SWOT analysis generated promotional strategies based on the strengths and weaknesses of tourism in CPT, 1) SO strategy by increasing the number of interesting vehicles adjusted to the local wisdom of the Perinci village community, so that it has its own distinct characteristics / uniqueness that is different from other tours; 2) ST Strategy by increasing the competitiveness of Coban Parang Tejo; 3) WO Strategy by increasing facilities / infrastructure and existing infrastructure; and 4) WT strategy by collaborating with investors and strengthening community communities. All of which are in the context of improving the welfare of the community.